Sociotechnical Imaginaries and Techno-Optimism: Examining Outer Space Utopias of Silicon Valley. (3rd July 2021) - Tutton, Richard
ABSTRACT: Silicon Valley entrepreneurs have been investing in improving human spaceflight capabilities through the development of reusable rockets to greatly reduce the cost of orbital launches. One such entrepreneur is the controversial Elon Musk who projects a techno-optimistic vision of the future in which humans live on other planets, enabled by his company's technologies. This is a technologically utopian and libertarian vision that has implications for ongoing contestations about the future of Earth and humanity. For Musk and his investors and supporters, their vision is about how human action in outer space will transform things 'down here', bringing about positive social change. While many celebrate such business leaders of Silicon Valley, critical voices challenge their evasion of current global challenges. Musk's techno-optimistic visions can be illuminated by the concept of sociotechnical imaginaries that draws attention to how public debates about science and technology also often evoke feelings of excitement, adventure, disappointment and anxiety. Science fiction narratives and digital simulations play an important role in conveying to multiple publics the desirability and feasibility of such imagined futures. However, although exciting in ambition and design, Silicon Valley visions of outer space futures offer little to the flourishing of humans and the planet.